A review of precision management for golf course turfgrass. Issue 2 (21st August 2022) - Carlson, Michael G.; Gaussoin, Roch E.; Puntel, Laila A.
Abstract: Precision turfgrass management (PTM) is a combination of methods and technologies proposed to increase the resiliency of golf courses by improving input efficiency while maintaining the function and aesthetics of the playing surface. However, there is no recent review describing the status of precision management in turfgrass. The objectives of this review were to (a) summarize peer reviewed research on precision technology for turfgrass management, (b) describe adoption of PTM‐based tools, and (c) propose an agenda of research priorities to advance and promote PTM adoption. Of the articles reviewed, 94% documented the accuracy of sensors to detect turfgrass performance and stressors before or during visual symptoms. Only 6% of the research reviewed focused on developing models or decision support systems to quantify the relationship among reflectance, nitrogen uptake, visual quality, biomass production, and irrigation which are required for precision management by golf course superintendents. Efficacy or value of using PTM methods and technologies have not been reported. Golf course superintendents lack of knowledge about PTM, and lack of quantification of benefits of PTM pose limitations to promote adoption. Increasing the adoption of PTM will require research to focus additionally on automating sensor data processing; quantifying costs, benefits, and value of adopting PTM; and simplifying input applications in a PTM system. This review described the status of precision management in golf course turfgrass and shed light into the need for research to develop models and decision support tools for precision management of golf course turfgrass. Core Ideas: Precision turfgrass management is proposed to increase golf course resiliency. Research has focused on measuring performance and stressors of turfgrass. Superintendents' lack of knowledge about precision turfgrass management poses a challenge toward future adoption. Future research should focus on developing precision turfgrass management decision support systems for golf course turfgrass.